Plasmonic tooth-multilayer structure with high enhancement field for surface enhanced Raman spectroscopy. (23rd February 2017) - Huang, Li-Chung; Wang, Zhiyu; Clark, J Kenji; Ho, Ya-Lun; Delaunay, Jean-Jacques
Abstract: The significant enhancement seen in surface-enhanced Raman scattering (SERS) heavily relies on the ability of plasmonic structures to strongly confine light. Current techniques used to fabricate plasmonic nanostructures have been limited in their reproducibility for bottom-up techniques or their feature size for top-down techniques. Here, we propose a tooth multilayer structure that can be fabricated by using physical vapor deposition and selective wet etching, achieving extremely small feature sizes and high reproducibility. A multilayer structure composed of two alternating materials whose thicknesses can be controlled accurately in the nanometer range is deposited on a flat substrate using ion-beam sputtering. Subsequent selective wet etching is used to form nanogaps in one of the materials constituting the multilayer, with the depth of the nanogaps being controlled by the wet etching time. Combining both techniques can allow the nanogap dimensions to be controlled at sub 10 nm length scale, thus achieving a tooth multilayer structure with high enhancement and tunability of the resonance mode over a broad range, ideal for SERS applications.